Veblenian Consumption in the Digital Age: Self-Image, Social Status, and the Performance of Distinction - Anita Kristina; Auliyah Elsa Tsaniyah; Kamsin, Khairunisah (The Journal of Society and Media, 2026)
This study examines the contemporary manifestation of Veblenian conspicuous consumption within the digital sphere, addressing its urgency in understanding evolving social dynamics and self-presentation in the internet age. The central problem investigated is how individuals utilize digital platforms, specifically Instagram, to perform distinction and enhance self-image and social status through consumption. Employing a netnographic methodology, data was primarily collected through scrolling observation of user profiles and in-depth interviews conducted via Direct Message (DM) on Instagram. Findings reveal that digital conspicuous consumption, characterized by the curated display of goods and experiences, significantly contributes to individuals' self-perception and their perceived position within social hierarchies. This phenomenon is analyzed through the lens of Veblen's theory, highlighting how digital spaces amplify the performative aspects of consumption. The research contributes to the fields of consumer behavior and economic psychology by providing a nuanced understanding of how traditional theories of consumption adapt and manifest in the digitally mediated environment